A Project by Andrea Lilio for the church of San Francesco a Ripa in Rome - Marcelli, Fabio (Eikón / Imago, 2020)
This essay is dedicated to a model for an altarpiece by Andrea Lilio, depicting the blessed Pedro de Alcántara and Pascual Baylón. This project can be dated to 1622-1623, just after the beatification of friar Pascual (1618) and friar Pedro (1622). It was the first altarpiece depicting the two Spanish blessed in the city of Rome, for a chapel dedicated to them in the ancient church of San Francesco a Ripas.